Sex-specific contributions to nest building in birds. (21st July 2021) - Mainwaring, Mark C; Nagy, Jenő; Hauber, Mark E
Abstract: The causes and consequences of interspecific variation in sex-specific contributions to animal parental care are relatively well understood during pregnancy or incubation and during offspring provisioning, but comparative patterns of sex-biased investment during nest-, den-, or other shelter-building have been almost completely overlooked. This is surprising because birthing shelters' protective properties have important fitness consequences for both parents and offspring. Here, we address this gap in our knowledge by testing predictions concerning sex-specific contributions to avian nest building in more than 500 species of Western Palearctic birds in relation to the time available to breed and sex-specific reproductive effort, while also examining correlates with nesting site and nest structure. Using multivariate phylogenetic comparative and path analysis approaches, we found that, opposite to what had been predicted, species in which females build nests alone have shorter breeding seasons and breed at higher latitudes. In addition, species in which females lay larger clutch sizes and incubate eggs alone are more likely to have nests built by females alone, again countering predictions that reproductive contributions are not traded-off between the sexes. Finally, however, sex-specific nest building contributions were predictably related to nest site and structure, as species in which females built nests alone were more likely to have open cup nests relative to enclosed, domed nests of species in which both parents build. Our study provides important new insights, and generates several new questions for experimental research into the adaptive dynamics of sex-specific contributions prior or at the onset of parental care. Abstract : We examined sex-specific parental contributions to nest building and using data from >500 species of European birds, showed that species in which females build nests alone breed at higher latitudes, have shorter breeding seasons, female-only incubation and larger clutch sizes than species in which both sexes contribute. Meanwhile, species in which females build nests alone construct smaller and simpler open cup nests than the domed nests built by males and females together.